The complementary in the reality - Luna, Verónica (Universidad de Cuenca, 2013)
The built space has evolved and those who occupy this space have not maintained the pace of this evolution. It is necessary to create new organs to extend our senses and our body to new dimensions still unimaginable and maybe impossible, it is necessary to re-signified the reality. Art and architecture may be the last resort of freedom that we have for the reflection of what actually happens with the already built and about the place that we are leaving to our children.The imagined city, the territories, the imaginary and the symbolic.Keywords: Art, architecture, urban imaginaries.